Toy library a feasibility study for Marikina City - Deasis, Susannah V.; Gonzales, Grace Marie B.; Tongson, Excelsa C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
This is a descriptive-feasibility study that determined the viability of setting up the first ever statutory toy library in Marikina City according to its market, technical, and financial aspect. A total of 200 parent/guardian respondents were interviewed in 2005. Respondents were evenly distributed among the 15 barangays of Marikina City according to its population percentage.
All data obtained were summarized, while market sub-objective data were also tested for significant associations with the toy library's technical requirements (e.g. location, time, etc.).
This study can also be considered one of the pioneering studies on toy libraries in the Philippines. An exhaustive and lengthy review of the related literature on toy libraries and play were Discussed in Chapter II.
Results showed that it is feasible to establish a toy library in Marikina City considering respondents overwhelming positive response on the importance of play for their child's development. Local government of Marikina City is also very willing to financially and logistically support such project, and at the same time, is also capable of doing so since the city is well established and excelling in almost every aspect of its governance. Other agencies were also considered for support especially for the library's sustainability. Technical requirements of the proposed toy library were also listed based on the respondents' preferences.
Vita.
Thesis (Master of Library and Information Science)--University of the Philippines Diliman
Keywords: Toy lending libraries -- Philippines -- Marikina City